Helheim Glacier Poised for Dramatic Retreat - Williams, Joshua J.; Gourmelen, Noel; Nienow, Peter; Bunce, Charlie; Slater, Donald (Geophysical research letters, 2021)
Helheim Glacier, one of the largest marine‐terminating outlet glaciers draining the Greenland Ice Sheet, underwent significant retreat and acceleration in the early 2000s, accounting for an appreciable proportion of the ice sheet's mass loss during that period. Using a range of remotely sensed datasets, we show that despite a subsequent readvance, the glacier has continued to lose mass and thin, and has retreated inland of the retracted position occupied in 2005. Critically, the near‐terminus is up to 100 m thinner than during 2005, and the front 5 km is within 25–50 m of flotation, with retrograde bed slopes extending several kilometers inland of the terminus. The neighboring Fenris and Midgard Glaciers have both undergone recent large‐scale and rapid retreat once their near‐terminus regions began to float, suggesting that under projected climate warming and associated glacier thinning, Helheim Glacier is poised to pass a threshold whereby the near‐terminus region will retreat rapidly. Plain Language Summary A significant proportion of the Greenland Ice Sheet's contribution to global sea‐level rise is as a result of mass loss from its marine‐terminating glaciers. Helheim Glacier, located in southeast Greenland, is one of the largest and fastest‐flowing glaciers draining the Greenland Ice Sheet. During the early 2000s, Helheim Glacier underwent dramatic retreat and acceleration, but subsequently readvanced during relatively cooler conditions in 2006. However, persistently high ocean and atmospheric temperatures have meant that Helheim Glacier has in fact been continuously losing mass since 2003, despite this readvance. Here, we use a range of remotely sensed data to show that since 2014, Helheim Glacier has accelerated and retreated to a greater extent than occurred in 2003–2005. More importantly, as the glacier has been losing mass over the past two decades, it is currently much thinner than during its peak retreat in 2005. As the glacier continues to lose mass, it will pass a threshold whereby the ice will float and rapidly disintegrate. We observe that this process has already occurred at the glaciers neighboring Helheim Glacier, which are subject to the same climate forcing and thus provide an analogue for the future response of Helheim Glacier to continued warming. Key Points Helheim Glacier is more retreated and the near‐terminus region is up to 100 m thinner than during its much‐reported dramatic retreat in 2005 Helheim, one of Greenland's largest ice dischargers, is now more vulnerable than at any point since the Little Ice Age Helheim's new configuration offers potential for sustained dynamic instability and a major contribution to global sea‐level rise